A Late Middle Pleistocene Climatic Cycle in Southern Italy Inferred From Pollen Analysis and Tephrostratigraphy of the Acerno Lacustrine Succession - Munno, Rosalba; Petrosino, Paola; Romano, Paola; Russo Ermolli, Elda; Juvigné, Étienne (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2001)
Abstract The Acerno lacustrine basin represents a tectonic palaeolake formed in the southern Apennines during the Middle Pleistocene. Pollen analysis performed on the lacustrine sequence (about 100 m thick) allows the vegetation history to be reconstructed and correlated with a late Middle Pleistocene interglacial-glacial cycle. Interglacial conditions are evidenced by a rich oak forest phase while the glacial period is highlighted by a sharp decrease in all arboreal taxa and by the contemporaneous increase in herbaceous and steppe elements. The absence of subtropical elements such as cf. Taxodium and Carya throughout the sequence suggests a late Middle Pleistocene age on the basis of comparison with the nearby Vallo di Diano palaeolacustrine basin where these elements survived until the end of isotopic stage 13. Analysis of the thickest tephra layers identified throughout the sequence provide further constraints to better define its chronological position which is correlated with isotopic stages 9 and 8 by the presence of the Lower WTT (White Trachytic Tuff) marker level, dated 297 000 yr BP.